STRENGTHENING REGULATION OF UNMANNED AIRCRAFT (DRONE) THROUGH LAW - Al Huda, Mukhlis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
The development of science and technology has brought the world into the Revolution Industrial 4.0. The Industrial Revolution is marked by artificial intelligence, robotics, ecommerce, nanotechnology, automatic cars, and other innovations. Technological innovations in the world of aviation are unmanned aircraft that have begun to be used for various civilian to military purposes. Observing the increasingly massive use and utilization of unmanned aircraft, the Indonesian government through the Ministry of Transportation has issued a Regulation of the Minister of Transportation Number PM 180 of the Year concerning Control of Operation of Unmanned Aircraft Systems in Airspace Served by Indonesia and renewed by Regulation of the Minister of Transportation Number PM 47 Year 2016 concerning Amendments to the Regulation of the Minister of Transportation Number PM 180 of 2015 concerning Control of Operation of Unmanned Aircraft Systems in Airspace Served by Indonesia. Apart from having a positive impact on civilian and military activities, unmanned aircraft also have a negative impact because they are used for crimes ranging from reconnaissance, drug delivery to theoreticalism. In the Permenhub which regulates unmanned aircraft there is only administrative sanction, therefore there must be a strengthening of the regulation of unmanned aircraft which contains criminal sanctions through the Law